Personal Liberty and Public Good : the Introduction of John Stuart Mill to Japan and China. - Howland, Douglas R. (University of Toronto Press, 2014)
Personal Liberty and Public Good is a compelling addition to the corpus of writing on the work of John Stuart Mill. It will be of great interest to historians of political thought, liberalism, and translation, as well as scholars of East Asian studies.